MAKING OF BASIC ENGINEERING APPLICATIONS USING BADMINTON GAME MACROMEDIA FLASH 8 PROFESSIONAL - Iwan Kusmawandi; Munich Heindari Eka Sari, SKom, MMSI (Jurnal Sistem Informasi, 2010)
One method of manufacture that can be practically effective in the process of understanding the basic game of badminton is to use multimedia methods, because this method has the ability to  be able to show a combination of text, images, animation, sound, graphics, and interactivity. With this method Badminton lovers can learn how to play badminton from a multimedia application which is the intermediary of the science presented. Multimedia application made by the author with a theme of Association  -  Badminton Games Association, and is expected to provide an alternative learning activities, especially regarding badminton. By making an application that uses the computer media and multimedia methods. It is expected that the information and images displayed can be more dynamic, more interesting and more interactive.